Persuasionsstrategien in deutschen rechtsorientierten Zeitungen.: Eine korpuslinguistische Studie - Flinz, Carolina (Linguistik Online, 2019)
Corpus Linguistics has often proved fruitful to examine different types of discourses, also the one of refugees. Aim of the paper is to show how language usage patterns can be focused on with the help of techniques grounded in Corpus Linguistics, giving information about themes and topoi. After showing what type of words (keywords, collocations) and what type of phenomena will be considered (topoi, metaphors and frames) in the article, the focus will shift on the methodology and the adopted criteria. After presenting the primary corpus (articles from right-oriented newspapers) and the comparison corpus (articles from Die Zeit) the main results of the analysis are presented and reflected on.